2011
DOI: 10.1536/ihj.52.27
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Six Novel SCN5A Mutations in Japanese Patients With Brugada Syndrome

Abstract: SummaryMutations in SCN5A are linked to Brugada syndrome in approximately 20% of all cases (BrS1). Several dozen distinct SCN5A mutations in BrS1 have been associated with the increased risk of cardiac arrhythmias. However, the genotype-phenotype relationship remains elusive. The current study analyzed the SCN5A gene to elucidate the potential variability of clinical features in Japanese BrS1 subjects. Subjects of the present study included 30 probands (25 male subjects, 45 ± 15 years of age) with Brugada-patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…All coding exons of desmosome genes (JUP, DSP, PKP2, DSG2, and DSC2) and their splice sites were amplified by polymerase chain reaction (PCR) using primers flanking the intronic sequences as reported previously. 15 The PCR products were purified and directly sequenced using an ABI PRISM 3130 Genetic Analyzer (Applied Biosystems, Foster City, CA, USA). The rare variants were analyzed at least twice by independent PCR amplification and sequencing.…”
Section: Genetic Analysismentioning
confidence: 99%
“…All coding exons of desmosome genes (JUP, DSP, PKP2, DSG2, and DSC2) and their splice sites were amplified by polymerase chain reaction (PCR) using primers flanking the intronic sequences as reported previously. 15 The PCR products were purified and directly sequenced using an ABI PRISM 3130 Genetic Analyzer (Applied Biosystems, Foster City, CA, USA). The rare variants were analyzed at least twice by independent PCR amplification and sequencing.…”
Section: Genetic Analysismentioning
confidence: 99%
“…The p.R1193Q substitution was previously shown to accelerate inactivation of the sodium channel current [5]. This substitution has been identified in patients with Brugada syndrome [5,6] and long QT syndrome [4,7]. The p.R1193Q substitution has been characterized functionally as either a "loss-of-function" variant consistent with Brugada syndrome [5], or as a "gain-of-function" variant consistent with previously defined long QT syndrome type 3 [4].…”
Section: Introductionmentioning
confidence: 97%
“…It was reported that the R1193Q substitution accelerates the inactivation of the sodium channel current [4]. The R1193Q substitution was identified in patients with Brugada syndrome [4,9] and long QT syndrome [8,10]. The R1193Q substitution has been characterized functionally as either a ''loss of function'' variant consistent with Brugada syndrome [4], or a ''gain of function'' variant consistent with previously defined long QT syndrome type 3-causing substitution [8].…”
Section: Discussionmentioning
confidence: 99%